PENGEMBANGAN POTENSI DESA DAN PERLUASAN JARINGAN PEMASARAN MELALUI E-COMMERCE LOKAL BAGI PELAKU INDUSTRI RUMAHAN - Maimun; Tarmizi (CV. Naskah Aceh, 2022)
Nowadays, the development of Micro, Small and Medium Enterprises (MSMEs) is supported by technological developments. The existence of the industrial revolution 4.0 has had a positive impact on the development of the business world. The appropriate use of cutting-edge technology in business development based on an established entrepreneurial spirit will be able to optimize the process as well as the results of the business unit being developed. E-commerce training in the home industry provides benefits to Micro, Small and Medium Enterprises in Sukajaya Muara Tiga Village to increase sales turnover and be able to develop the business they are running so that it grows even bigger. With this e-Commerce website, customers are not only from Sukajaya Muara Tiga Pidie Aceh, but customers can be from Sukajaya Muara Tiga and even outside Aceh, of course it can help the government in improving the economy, especially in village areas, so that village areas become open. the opportunity to be able to compete on the national and international stage. The ordering process, sales process and stock of goods can be done quickly and accurately so that it can help monitor business and of course can increase sales turnover for MSMEs in Sukajaya Muara Tiga Village.